1983
DOI: 10.1104/pp.73.2.434
|View full text |Cite
|
Sign up to set email alerts
|

Light and Shade Effects on Abscission and 14C-Photoassimilate Partitioning among Reproductive Structures in Soybean

Abstract: Field experiments were conducted in 1981 and 1982 to study the effects of low-irradiance supplemental light on soybean (Glycine max [L.] Merr. cv Evans) flower and pod abscission. Cool-white and red fluorescent lights illuminated the lower part of the soybean canopy during daylight hours for 3 weeks late in flowering. At the same time, flowers and young pods on half the plants were shaded with aluminum foil. Flowers were tagged at anthesis and monitored through abscission or pod maturity.Responses to red and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 19 publications
2
51
0
1
Order By: Relevance
“…They found the greatest reduction in yield by shading the canopy shortly after R5. Although they also found that light enrichment by using a refl ector before R5 had a greater effect on yield than that after R5, the light enrichment inside the canopy using a refl ector might not only increase assimilate supply, but also have a photomorphogenic effect on pod development (Heindl and Brun, 1983). Yoshida et al (1983) observed the dimensional growth of reproductive organs in fi eld-grown determinate and indeterminate cultivars, and showed that pods reached maximal length and width within a few weeks after R5.…”
Section: Resultsmentioning
confidence: 99%
“…They found the greatest reduction in yield by shading the canopy shortly after R5. Although they also found that light enrichment by using a refl ector before R5 had a greater effect on yield than that after R5, the light enrichment inside the canopy using a refl ector might not only increase assimilate supply, but also have a photomorphogenic effect on pod development (Heindl and Brun, 1983). Yoshida et al (1983) observed the dimensional growth of reproductive organs in fi eld-grown determinate and indeterminate cultivars, and showed that pods reached maximal length and width within a few weeks after R5.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, grain set was not affected when photosynthesis was completely inhibited by treatment with DCMU, indicating that the reduction of set was not mediated by photosynthesis. It also has been reported that shading flowers and pods increased abscission and reduced accumulation of photoassimilate in soybean (9).…”
mentioning
confidence: 99%
“…Some studies have implied that reproductive abscission in legumes is hormonally mediated (6,8,12,14), while others have implied that it is related to> the availability of photosynthetic assimilates (4, 10, 11). However, since reproductive abscission occurs at a time when plant photosynthetic rate is relatively high and reproductive growth rate is relatively low, it appears not to be limited by the contemporary supply of photoassimilate.…”
Section: Introductionmentioning
confidence: 99%